2021
DOI: 10.3390/ijms22084059
|View full text |Cite
|
Sign up to set email alerts
|

Kinetically Equivalent Functionality and Reactivity of Commonly Used Biocompatible Polyurethane Crosslinking Agents

Abstract: In this paper, the kinetics of the reaction of phenyl isocyanate with crosslinking agents such as sucrose, sorbitol, and glycerol are reported. Crosslinking agents were used in high molar excess to isocyanate to obtain pseudo-first-order rate dependencies, and the reaction products were separated by high-performance liquid chromatography and detected by UV spectroscopy and mass spectrometry. It was found that the glycerol’s primary hydroxyl groups were approximately four times reactive than the secondary ones.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…To form crosslinks, based on one of our previous papers [ 31 ], sucrose dissolved in DMSO was added in 0.1 equivalent to PU-prepolymers. As shown in Scheme 1 , sucrose participates as netpoints in the formation of the crosslinked structure through its most reactive 6,6′ and 1′ primary hydroxyl groups [ 33 ]. The polyurethane prepolymers of different chain lengths can affect flexibility and the crosslink density of the resulting polyurethanes.…”
Section: Resultsmentioning
confidence: 99%
“…To form crosslinks, based on one of our previous papers [ 31 ], sucrose dissolved in DMSO was added in 0.1 equivalent to PU-prepolymers. As shown in Scheme 1 , sucrose participates as netpoints in the formation of the crosslinked structure through its most reactive 6,6′ and 1′ primary hydroxyl groups [ 33 ]. The polyurethane prepolymers of different chain lengths can affect flexibility and the crosslink density of the resulting polyurethanes.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we investigated the reaction of unprotected sucrose hydroxyl groups with phenyl isocyanate and found that the sterically and electronically less hindered primary hydroxyl groups (in the positions of 6 and 6 ) are more reactive than the third one in the position of 1 [28]. Based on this finding, we assumed that long linear chains could be synthesized using HDI and MDI.…”
Section: Synthesis Of the Sucrose-hdi Cooligomermentioning
confidence: 99%
“…The determination of the virtual UV area of the polyol was performed according to our previous report. 28 The plot for the values of A sum /A IS as a function of time can be found in the ESI † (Fig. S3, ESI †).…”
Section: And (3)mentioning
confidence: 99%